Algunos factores quirúrgicos y ansiedad pre operatoria en cirugía ambulatoria en el Instituto Regional de Oftalmología - Silva Gamarra, Gladys Wendy (2014)
The present study of descriptive guy correlacional and crosscut, ERP came true in patient adults submitted to day surgery in the Regional Institute of Oftalmología of Trujillo, with the aim of determining the relation between some surgical factors and the anxiety operative in the patient adults, using two instruments for the collection and evaluation of data, the inventory of self-assessment IDAREN and an opinion poll to determine the surgical factors. For the statistical analysis SPSS used the statistical package himself version 19 for Windows XP and the independence test of criteria Chi – square; As well as the correlation coefficient of Pearson. A significant correlation between the surgical factors found previous surgeries and education ERP operative, and anxiety ERP operative.